The Role of Stock Returns, Financial Literacy, and Risk Perception in Shaping Investment Decisions through Ajaib Application Users - Anisya Dwi Deviyanti; Vicky Oktavia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research explores the impact of stock returns, financial literacy, and risk perception on investment decisions among Generation Z investors who use the Ajaib application in Indonesia. The study is driven by the increasing involvement of young digital investors and the growing importance of financial knowledge, risk awareness, and return expectations in shaping their behavior. A total of 250 respondents were surveyed, and the data were processed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that stock returns (β = 0.436, p < 0.001), financial literacy (β = 0.429, p < 0.001), and risk perception (β = 0.209, p = 0.002) each exert a positive and significant influence on investment decisions. The model explains 68% of the variance in investment decisions (R² = 0.626), confirming the robustness of the proposed framework. These results suggest that Gen Z investors with higher financial literacy, stronger risk awareness, and favorable return expectations are more likely to make confident and deliberate investment choices. The study contributes theoretically to behavioral finance literature and provides practical insights for improving financial literacy programs, enhancing investor education, and designing fintech features that foster trust. The findings can also inform policymakers in creating targeted initiatives to encourage responsible investment behavior among younger generations in Indonesia.